Manajemen Pendidikan Pesantren (Implikasi Resolusi Konflik Dalam Studi Kasus Di Pondok Pesantren Al-Ichsan Mojokerto) - Ali Muhsin (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2018)
Seen in the context of education management, the forms of conflict among pesantren elites caused by various factors, basically have dysfunctional implications on the management of education in pesantren. Conflicts have dysfunctional implications for the management of education, ie within the context of organizational structure, leadership context, the context of management functions, the context of management aspects and the loss of public trust. These five contexts affect each other and relate between one context and another. This study aims to obtain an in-depth picture of conflict resolution and management in pesantren with a qualitative approach. Pesantren has a deep-rooted tradition, namely the power (power) figures kiai in management. With the barakah system, the power (power) and authority of the kiai influence predominantly on institutional patterns, instruction and control of academic post in pesantren.